Impact of Carrageenan-Based Encapsulation on the Physicochemical, Structural, and Antioxidant Properties of Freshwater Snail (Bellamya bengalensis) Protein Hydrolysates - Anand Vaishnav; Naresh Kumar Mehta; Mocherla Bhargavi Priyadarshini; Soibam Khogen Singh; Pratap Chandra Acharya; Satyajeet Biswal; Harjeet Nath; Syed Arshad Hussain; Prasenjit Pal; Jham Lal; Nongthongbam Sureshchandra Singh; Bikash Kumar Pati (Colloids and Interfaces)
This study investigated the encapsulation of snail protein hydrolysates (SPHs) using carrageenan as a microencapsulating agent at concentrations of 1%, 2%, and 3%. SPHs were prepared from the soft tissue of freshwater snails (Bellamya bengalensis) through enzymatic hydrolysis using bromelain, resulting in a degree of hydrolysis of 48.05%. The encapsulation process was carried out using the spray-drying technique. Encapsulation with 3% carrageenan enhanced the yield, encapsulation efficiency (up to 84.96%), colloidal stability (up to −33.8 mV), and thermal stability (up to 75 °C). The particle size increased as the carrageenan concentration increased, reaching 206.9 nm at 3%, and the uniform polydispersity index (0.26) indicated stable encapsulation. While encapsulation reduces solubility and antioxidant activity (DPPH, FRAP, ABTS, and HRSA), it effectively protects SPH from environmental factors such as hygroscopicity and storage stability, thus maintaining high scavenging activity. Fourier transform infrared spectroscopy confirmed that carrageenan and SPH strongly interact. Scanning electron microscopy revealed that the particles had better shapes and smooth, cohesive surfaces. This study demonstrates the effectiveness of carrageenan as an encapsulating agent for SPH, enhancing its stability and bioactivity for potential applications in the food and nutraceutical industries as a bioactive additive and offering an alternative to conventional coating materials.